Non-linear mechanical characteristics of tailings in large-scale high tailings dams - Chen, Qinglin; Li, Zugui; Zhang, Chao; Dai, Zeyu; Wang, Xiaojun; Zhang, Xuepeng (Frontiers in Earth Science, 2023)
The nonlinear mechanical characteristics of tailings under high pressure are the research foundation for large-scale high tailings dams. In consider of the high stress caused by the high tailing pond, consolidated drained (CD) triaxial shear tests were carried out. The deterioration mechanism of nonlinear mechanics was revealed by particle crushing. The test results show that the samples density has a great influence on the volumetric strain under low pressure. However, volumetric strain is not related to the sample density under high pressure. The shear strength of the tailings shows a significantly nonlinear. The internal friction angle under low pressure be still obtained by the traditional linear Mohr-Coulomb, and the internal friction angle under high pressure be obtained by the power function Mohr criterion. The particle crushing of tailings not only occurs at high pressure but also at low pressure. The value of breakage index increases with the increase of sample density. The nonlinear mechanics of shear strength is affected by particle breakage. The value of breakage index increases linearly with the increase of the shear strength. It indicates that the large density in the deep part of the tailings dam is prone to the particle crushing, which affects the stability of the large-scale high dam.